(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
لقد اعتبر الباحثون أن هجوم النوكليوفيلات على الأزيريديناتN – المنشطة يحدث على ذرة الكربون C3 الأقل استبدالاً أو على ذرة الكربون C2 الأكثر استبدالا أو على ذرتي الكربون C2 وC3 للحلقة غير المتجانسة. غير أن الباحث ستام قد بين أن أنيون ثنائي هيدرو الانتراسين وأنيون الكسانتين يتفاعلان مع N – أسيل الأزيريدينات ليقود إلى النواتج الموافقة لفتح حلقة الأزيريدين من جهة الكربون C2. قمنا في بحثنا هذا بدراسة تفاعل N – بنزويل -2،2-ثنائي ميتيل الأزيريدين 1 مع مزيج من سيانيد البنزيل وNaH في THF عند درجة حرارة الغرفة ،حيث يتشكل البيروليدين 7 بمردود.(68%). إن دراسة بنية المركب 7 ، المحددة بواسطة مختلف الطرق الطيفية IR) 1HNMR و13CNMR وMS و(تؤكد أن فتح حلقة الأزيريدين قد تم من جهة الكربون C2. ولشرح آلية التفاعل، فاننا نقترح أنه قد وقع وفق آلية جذرية ممثلة بانتقال أحادي الكترون بين المركب 1 وأنيون سيانيد البنزيل ليقود للجذر الثالثي الأكثر ثباتا وذلك بتحطم متجانس للرابطة C2-N للمركب N - أسيل الأزيريدين 1 متبعاً بتحلق داخل جزيئي ثم باعادة ترتيب داخل جزيئية والحصول على المركب 7 الأكثر ثباتا بسبب الرابطة الهيدروجينية داخل الجزيئية. It has been shown that the nucleophiles attacked the activated aziridines on the less substitued C3 carbon or on the more substitued C2 carbon or on the C2 and C3 carbons of the heterocycle. However, Stamm has shown that the anion of dihydroanthracene and the anion of xanthene reacted with N-acylaziridines to give products resulting of the ring opening on the C2 carbon side of aziridine ring. In this work, we studied the reaction of the N-benzoyl-2,2-dimethylaziridine 1 with a mixture of benzyle cyanide and NaH in THF at room temperature. The structure of a new pyrrolidine 7 achieved by different spectrums data (IR, 1HNMR, 13CNMR, SM) and molecular modeling. The single electron transfert mechanism (radicalar mechanism) between the compound 1 and the anion of cyanide benzyle has been proposed to explain the formation of the product 7 (68%). The reaction product formed from the specific homolytic cleavage of the C2-N bond of N-acylaziridine 1 ; involving the more stable tertiary radical carbon which is subsequently ring closed and undergo the intramolecular rearrangements to give the corresponding pyrrolidine 7 which stabilised by intramolecular hydrogen bonding.